2001
DOI: 10.1128/jcm.39.5.1963-1966.2001
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Assay Targeting IS 481 of Bordetella pertussis and Molecular Basis for Detecting Bordetella holmesii

Abstract: Detection of Bordetella holmesii by a real-time PCR assay targeting IS481 of Bordetella pertussis is reported.Sequencing of IS481-specific PCR products from B. pertussis and B. holmesii isolates revealed sequence homology. Restriction fragment length polymorphism demonstrated a low copy number of IS481-like sequences in B. holmesii. These results, and culture of B. holmesii from patients with cough, suggest that the specificity and predictive value of IS481-based PCR assays for pertussis may be compromised.Bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
97
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 30 publications
4
97
1
3
Order By: Relevance
“…Only B. pertussis isolates gave bands of the expected size in the ptxA-Pr and IS481 assays. This is despite the reported presence of IS481-like elements in both B. holmesii (Reischl et al, 2001) and B. bronchiseptica (Gladbach et al, 2002). Explanations for the lack cross-reactivity with these two species using our IS481 PCR assay are: different sensitivities of the assays, the low and variable copy number of these elements in B. holmesii and B. bronchiseptica or the difference in the primer (probe) combination used and possible sequence variation in the target regions of these oligonucleotides.…”
Section: Pcr Sensitivity and Specificitycontrasting
confidence: 50%
See 1 more Smart Citation
“…Only B. pertussis isolates gave bands of the expected size in the ptxA-Pr and IS481 assays. This is despite the reported presence of IS481-like elements in both B. holmesii (Reischl et al, 2001) and B. bronchiseptica (Gladbach et al, 2002). Explanations for the lack cross-reactivity with these two species using our IS481 PCR assay are: different sensitivities of the assays, the low and variable copy number of these elements in B. holmesii and B. bronchiseptica or the difference in the primer (probe) combination used and possible sequence variation in the target regions of these oligonucleotides.…”
Section: Pcr Sensitivity and Specificitycontrasting
confidence: 50%
“…A PCR assay may be thought to be specific for an organism when it is designed, but subsequently it may be found that its target gene is present in other closely related, or even unrelated, organisms. Although in this study no amplification was seen with purified DNA from B. holmesii or B. bronchiseptica, the presence of IS481-like sequences in these two additional Bordetella species potentially compromises the use of such assays in establishing the specific presence of B. pertussis (Reischl et al, 2001;Gladbach et al, 2002). However, it appears that the greater sensitivity of IS481 assays (due to the presence of multiple copies) is a factor in their continued use by several laboratories.…”
Section: Comparison Of Pcr and Serologymentioning
confidence: 81%
“…Positive results should be followed by species-discriminating tests [33,34] to achieve diagnostic levels of specificity [28,31]. This test will not amplify sequence from B. parapertussis [33], and should not amplify from other known Bordetella species based on the apparent absence of the IS481 element outside of B. pertussis and B. holmesii [28,33].…”
Section: Bordetella Pertussismentioning
confidence: 99%
“…The first target, within the pertussis toxin S1 promoter (ptxP; previously denoted ptxA-pr), is specific for B. pertussis and is present at 1 copy per bacterial genome. The second target, the insertion sequence IS481, occurs in multiple copies in B. pertussis strains, but may also be present in strains of Bordetella parapertussis, Bordetella bronchiseptica and Bordetella holmesii (Muyldermans et al, 2005;Register & Sanden, 2006;Reischl et al, 2001;Fry et al, 2009). Despite the age restriction on the Health Protection Agency's diagnostic qPCR service, the number of pertussis cases confirmed by qPCR is increasing each year.…”
Section: Introductionmentioning
confidence: 99%